Studying the effect of Soluamine and Algamix seaweed extracts in some growth and yield characteristics of two types of barley - Ateka mohammad Nouri; Abdulaziz Shekho Abduljabbar (College of Education for Pure Sciences, 2013)
Abstract The experiment has been conducted at The Field to study The effect of three concentrations (0.0, 2.0, 4.0 ml/L.) of Algamix and Soluamine on plants. on growth and yield components of two Barley cultivars (AL - Jazeera 1 and Local barley). The sea weed concentrations of Algamix and Soluamine showed a great effect in increasing (the height of plants, inter nodes length, flag leaf area and tillers number). The two concentrations 2.0 and 4.0 ml/L. effect of both sea weed extracts showed a significant increase of (spike Length, grain number of spike, grain number of plant, weight of 1000 grain and yield characters of Barley cultivars).